Chronic jet lag reduces motivation and affects other mood-related behaviors in male mice - Acosta, Julieta; Crespo, Manuel T.; Plano, Santiago A.; Golombek, Diego A.; Chiesa, Juan J.; Agostino, Patricia V. (Frontiers in Physiology, 2023)
The circadian system regulates various physiological processes such as sleep-wake cycles, hormone secretion, metabolism, and the reaction to both natural and drug-based rewards. Chronic disruption of the circadian system caused by unsteady synchronization with light-dark schedules, such as advancing chronic jet lag (CJL), leads to adverse physiological effects and pathologies, and is linked with changes in mood and depressive behaviors in humans and rodent models. In the present work, a set of behavioral tests were performed in mice showing desynchronization of activityrest rhythm under CJL. Compared to controls under 24 h light-dark cycles, mood-related behaviors were affected, by decreasing motivation for food reward, increasing anhedonia, and inducing increased anxiety and depressive-like behaviors.Understanding the importance of the circadian system and its potential role for disruption due to CJL is important for maintaining good health and well-being.